A rare case of alpha-methyldopa-induced hepatitis in pregnancy - Likić-Lađević Ivana; Petronijević Miloš; Vrzić-Petronijević Svetlana; Beleslin Aleksandra; Dugalić Stefan (Srpski Arhiv za Celokupno Lekarstvo, 2024)
Introduction. There are three groups of disorders during pregnancy: disorders specific for pregnancy that resolve spontaneously or soon after delivery, acute hepatic disorders coinciding with pregnancy, and chronic disorders. Drug-induced liver disease prevails among women and it is estimated to be a leading cause of acute liver injury. Drug-induced hepatitis is rare in pregnancy with only a few cases reported in literature. Alpha-methyldopa is one of the commonly used drugs in pregnancy that could cause hepatotoxicity with different clinical presentations and possible adverse effects on normal course of pregnancy. Case outline. We reported a rare case of hepatotoxicity caused by alpha-methyldopa in 26 gestational weeks pregnancy in a 35-year-old patient admitted because of jaundice and elevated liver function tests. She had been using antihypertensive drug, alpha-methyldopa, from 12th gestational week, and no other medication or supplementation was recorded. Ultrasound of the abdomen excluded obstruction or any other abnormalities. Autoimmune panel was done. Biochemical analyses were indicative of toxic acute liver injury caused by alpha-methyldopa according to values of transaminase. After 13 days, patient was discharged recovered from the hospital. Conclusion. Diagnosis of alpha-methyldopa hepatotoxicity is challenging since the low incidence, unpredictability, diverse symptomatology and absence of specific biomarkers. That is why timely diagnosis is crucial for the well-being of both future mother and child.